Optimization of a formula to develop iron-dense novel composite complementary flour with a reduced phytate/minerals molar ratio from dabi teff-field pea-based blends using a D-optimal mixture design - Tura, Diriba Chewaka; Belachew, Tefera; Tamiru, Dessalegn; Abate, Kalkidan Hassen (Frontiers in Nutrition, 2023)
Iron deficiency anemia is one of the major public health problems in children associated with the inadequate intake of bioavailable iron. Thus, this research was aimed at incorporating dabi teff, an underutilized/forgotten crop, into other pre-processed local food crops, viz., germinated maize, roasted barley, roasted field pea, dehulled oats, and linseed, to develop optimized iron-dense novel composite complementary flour with a reduced phytate/minerals molar ratio. Nutrisurvey software was employed to define ranges, and they were constrained at 20–35% dabi teff, 0–30% field pea, and 5–20% maize, while the remaining were kept constant at 25% barley, 15% oats, and 5% linseed. Eleven experimental runs were generated from the six mixture components using Stat-Ease Design Expert® software version 11, D-optimal. Inductively coupled plasma-optical emission spectrometry was used to determine micronutrients. ‘Scheffe’ regression was used to fit and test the model’s adequacy, and numerical multi-response optimization was performed using the Design Expert® to identify the optimal points. Dabi teff had a significantly higher (p < 0.05) iron content at 86.5 mg/100 g, iron density at 24.53 mg/100 kcal, and calcium content at 123.59 mg/100 g. The new formulations had a significantly higher iron content (3.31–4.36 times), iron density (3.25–4.27 times), and calcium content (1.49–1.58 times), as compared to the control flour, and fulfilled FAO/WHO recommendations. The optimal formula was identified at 34.66% dabi teff, 25% barley, 15% oats, 15.34% field pea, 5% linseed, and 5% maize flour ratios, with response values at the overall optimization as 32.21 mg/100 g iron, 77.51 mg/100 g calcium, 2.59 mg/100 g zinc, 0.233 phytate/iron molar ratio (Ph:Fe), 0.067 phytate/calcium molar ratio (Ph:Ca), 3.43 phytate/zinc molar ratio (Ph:Zn), and 6.63 phytate by calcium to zinc molar ratio (Ph*Ca:Zn). Furthermore, it contained iron at a level that is 2.01 times higher than the standard and 4.44 times higher than the control, as well as an iron density of 8.47 mg/100 kcal, which was 4.39 times higher than that of the control. These findings showed that the optimized dabi teff-field pea based iron-dense novel composite complementary flour with enhanced bioavailability can be developed and used as a sustainable food-based strategy to combat iron deficiency anemia among children in less developed countries, such as Ethiopia.